RENEWAL OF CRIMINAL LAW IN THE CUSTOMARY LAW - Dhini Hindria Restuti (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
This research aims to find out the position of customary law in the renewal of criminal law and also main difference between the Indonesia Criminal Code and Custom Criminal Law. The research method used in this research is qualitative normative juridical approach. In this research we are able to find the result, that is, if the Customary Law acts as the source of law in the Renewal of Criminal Law, then it can be seen from the angle of policy approach. First, as part of social policy. Second, as part of criminal policy.Third, as part o law enforcement policy. Then the main differences between the Indonesia Criminal Code and Custom Criminal Law lie in the subject of Law, deliberate or mistake, the crime doer, trial offence, nature of offence.